Insight into the mechanisms regulating liver cancer stem cells by hepatitis B virus X protein - Xiaocui Li; Delong Kong; Wei Hu; Kuiyang Zheng; Hongjuan You; Renxian Tang; Fanyun Kong (Infectious Agents and Cancer)
Abstract Hepatocellular carcinoma (HCC) is a heterogeneous disease with high recurrence and mortality. It is well known that a large proportion of HCCs are caused by hepatitis B virus (HBV) infection. In particular, the HBV X protein (HBX), a multifunctional molecule produced by the virus, plays a leading role in hepatocarcinogenesis. However, the molecular mechanisms underlying HBX-mediated HCC remain not fully elucidated. Recently, liver cancer stem cells (LCSCs), a unique heterogeneous subpopulation of the malignancy, have received particular attention owing to their close association with tumorigenesis. Especially, the modulation of LCSCs by HBX by upregulating CD133, CD44, EpCAM, and CD90 plays a significant role in HBV-related HCC development. More importantly, not only multiple signaling pathways, including Wnt/β-catenin signaling, transforming growth factor-β (TGF-β) signaling, phosphatidylinositol-3-kinase (PI-3 K)/AKT signaling, and STAT3 signaling pathways, but also epigenetic regulation, such as DNA and histone methylation, and noncoding RNAs, including lncRNA and microRNA, are discovered to participate in regulating LCSCs mediated by HBX. Here, we summarized the mechanisms underlying different signaling pathways and epigenetic alterations that contribute to the modulation of HBX-induced LCSCs to facilitate hepatocarcinogenesis. Because LCSCs are important in hepatic carcinogenesis, understanding the regulatory factors controlled by HBX might open new avenues for HBV-associated liver cancer treatment.